FERULA (Ferula spp.) – MEDICINAL PROPERTIES AND GROWING METHODS (Ta'limning zamonaviy transformatsiyasi, 2024)
This article explores the medicinal properties of the Ferula species, its distribution, chemical composition, and traditional usage in medicine. It also discusses the best methods for cultivating this unique plant.